An improved direct RNA sequence method; its application to Vicia faba 5.8S ribosomal RNA. - Tanaka, Y (Nucleic Acids Res, 1980)
We have developed a direct read-off sequencing procedure, based on the method of Stanley and Vassilenko using E. coli 5S ribosomal RNA as a model compound. Radioactive bands were transferred from an acrylamide gel fractionation in the first dimension onto a DEAE-cellulose thin layer plate. After in situ enzymatic digestion with RNase T2, mononucleoside 3',5'-diphosphates were separated in the second dimension by electrophoresis at pH 2.3. Using this two-dimensional procedure the entire sequence of 163 residues of the previously unknown Vicia faba (broad bean) 5.8S ribosomal RNA was deduced. IMAGES: